Torquigener flavimaculosus Hardy and Randall, 1983 (Pisces: Tetraodontidae) off Rhodes island marine area: a new alien fish in the Hellenic waters - CORSINI-FOKA, M.; MARGIES, P.; KONDILATOS, G.; ECONOMIDIS, P.S. (Mediterranean Marine Science, 2006)
The presence of the pufferfish Torquigener flavimaculosus was recorded during the winter 2006-2007 off Rhodes Island (SE Aegean Sea). The species, known from the western Indian Ocean, has established populations from the Levantine basin to Fethiye, Turkey. This finding expands the known range of the species in the Mediterranean to the south-eastern Aegean Sea.